2023
DOI: 10.3390/app13179590
|View full text |Cite
|
Sign up to set email alerts
|

Solar Sail Transfer Trajectory Design for Comet 29P/Schwassmann–Wachmann 1 Rendezvous

Alessandro A. Quarta,
Karim Abu Salem,
Giuseppe Palaia

Abstract: The goal of this paper is to analyze the optimal transfer towards the periodic comet 29P/Schwassmann–Wachmann 1 of a solar sail-based spacecraft. This periodic and active comet is an interesting and still unexplored small body that has been regarded as an object of the Centaurs group. In this work, a classical (heliocentric) orbit-to-orbit transfer is studied from an optimal viewpoint, by finding the spacecraft trajectories that minimize the flight time for a given value of the solar sail characteristic accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The value of n can be estimated using an analytical expression obtained through the combination of Equations ( 6), (25), and (28). Indeed, assuming ãp sin α ≃ ãm sign r f − 1 during the transfer, with the aid of Equation ( 28), the second and the last of Equation ( 6) give…”
Section: Maximum Value Of ãM Compatible With the Proposed Methodsmentioning
confidence: 99%
“…The value of n can be estimated using an analytical expression obtained through the combination of Equations ( 6), (25), and (28). Indeed, assuming ãp sin α ≃ ãm sign r f − 1 during the transfer, with the aid of Equation ( 28), the second and the last of Equation ( 6) give…”
Section: Maximum Value Of ãM Compatible With the Proposed Methodsmentioning
confidence: 99%
“…The RTN reference frame is schematized in Figure 3, which is an adaptation of a similar figure that has recently appeared in Ref. [27]. Note that the plane ( îR , îT ) coincides with the plane of the spacecraft osculating orbit.…”
Section: Spacecraft Dynamics In the Interplanetary Spacementioning
confidence: 96%
“…The set of classical orbit elements can be recovered by inverting Equation (1), as described in Ref. [27], and the result is…”
Section: Spacecraft Dynamics In the Interplanetary Spacementioning
confidence: 99%
“…The problem under consideration, that is, the calculation of the optimal control law (or, equivalently, the optimal transfer trajectory) that satisfies the final conditions of Equation ( 5) and minimizes the value of a c , is solved using an indirect approach based on the calculus of variations [36,37]. The mathematical model requiring the definition of the Hamiltonian function and the (numerical) integration of the Euler-Lagrange equations is similar to the model discussed by the authors in the recent paper [38], and is not reported here for the sake of conciseness. However, it is interesting to mention that the optimal sail pitch angle is determined, according to Sauer [35], using Pontryagin's maximum principle [39], while the boundary value problem associated with the optimization process is solved numerically by adapting the procedure described in [40].…”
Section: Mathematical Model Of the Solar Sail-based Transfermentioning
confidence: 99%